Struktur Komunitas Fitoplankton sebagai Bio Indikator Kualitas Perairan Danau Rawapening Kabupaten Semarang Jawa Tengah - Wijaya, Trian Septa; Hariyati, Riche (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
Rawapening is a distric of lake equatorial which has many potential benefit such as fishery, recreation facilities, Eceng gondok plant, etc. The water quality there is damagedend disturbed by fishery increacing and Eceng gondok growth. The changeness of equatorial quality can be identifies by richness of fitoplankton’s compotition. That is because fitoplankton makes an important contribution in equatorial ecosistem as primer produsen in food equilibrium and that can respons the environment’s change. The sampling’s dot is chosen by sampling random methode in five different sampling dot including the area of Kali galeh, Bukit cinta, Asinan, Seraten, and Tuntang. The primer parameter in this research is the community structure of fitoplankton and the secondary parameter is physic and chemis factor in equatorial ecosistem like pH, turbidity, temperature, brightness, speed of waves and oxygen demand. The result of this observatory found 16 genus of fitoplankton that consist of 4 division : 5 genus of Chrysophyta, 6 genus of Chlorophyta, 3 genus of Cyanophyta and 2 genus of Dynophyta. Most of fitoplankton population is dominated by spesies of Melosira. The saprobik index shows value 1,63 that indicated the water of equatorial ecosistem is poluted low in Oligo fase / β- mesosaprobik.